KONSEP DUNIA DIGITAL MELALUI METAVERSE DAN KAITANNYA DENGAN PERKEMBANGAN INDUSTRI KREATIF - Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom, Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2023)
2022 is predicted to be the biggest year for the metaverse, as Meta, Apple, Microsoft and Google are all set to release new hardware products and software services that can sustain new developments in the world of technology today and in the future. The next question for the community is what is meant by this Metaverse? What's the definition? What is its relevance and potential now and in the future? What technologies were directly involved in the development of this Metaverse? How is the Metaverse with the Creative Media Industry, especially the animation industry and the game industry? Methods The research is carried out with a qualitative method. The system used is a descriptive exploration system. The data collection method used is a literature study by looking for reference propositions that are applicable to cases or problems. Metaverse will be realized, because the technology needed to create a metaverse is already available, such as capable mobile device processors and game consoles, adequate internet infrastructure, and the existence of VR headsets and cryptocurrencies. And the most important thing, is that people are getting used to living in the online world because of the pandemic. But besides its growth Metaverse has obstacles in its growth? Are consumers or society all interested in the metaverse? Are there any problems with the law and its protection for users?